Penerapan Metode Simple Additive Weighting untuk Meningkatkan Efisiensi pada Pemilihan Mahasiswa Berprestasi - Dismas Banar Purnandi; Ika Nur Fajri; Hendra Kurniawan (JURIKOM (Jurnal Riset Komputer), 2023)
Poltekkes Kemenkes Yogyakarta is one of the higher education institutions that has an Mahasiswa Berprestasi program that gives awards to outstanding students who meet the requirements based on predetermined criteria. The Selection of Mahasiswa Berprestasi at the Poltekkes Kemenkes Yogyakarta has so far started with collecting student data, then calculating the results of the scores obtained by each student starting from calculating the value of each student's criteria which will be multiplied by the weight of each predetermined criterion and then the total of all scores obtained is added up with calculator or Microsoft Excel. This can result in errors in the calculation of the results (human error) such as data input errors to be processed, to perform calculations requires a long time and more effort so that the alternative calculation results obtained are inaccurate. Making a website-based Decision Support System that will be built using database MySQL, the programming language using Hypertext Preprocessor (PHP) with the CodeIgniter 4 framework by applying the Simple Additive Weighting (SAW) method because the SAW method can select the best students from a number of students registered to receive student achievement awards. In addition, data collection was carried out using interview and observation methods as well as methods in system development using methods waterfall. The results of calculations using the SAW method manually with system calculations have 100% similarity in results with Nabilah Fathiyah Rahmah who obtained the first stage with a score of 0.986 then Wahyu Adi Pratama with a score of 0.943 and then to the last stage was obtained by Riska Annisa Putri with a score of 0.637.